Modifications in Chemical, Physical and Mechanical Properties of Nebbiolo (Vitis vinifera L.) Grape Berries Induced by Mixed Virus Infection - Santini, D.; Rolle, L.; Cascio, P.; Mannini, F. (South African Journal of Enology and Viticulture, 2011)
Modifications in grape quality parameters induced by mixed infection with GFLV and GFkV, GLRaV-1 and GVA, and GLRaV-3 and GVA in three Nebbiolo clones were compared against healthy plants of the same clones in two experimental vineyards in Piemonte, northwest Italy. The aim of the study was to evaluate the effect of virus infection on the mechanical properties of the berry skin and the whole berry as assessed by texture analysis tests, and on the amount and quality of berry skin phenols. Differences were observed in grapevine vigour, yield and juice composition, depending on the viral status of the plants. The anthocyanin profile of the vines infected with GFV and GFkV and those infected with GLRaV-1 and GVA showed a lower percentage of the more stable tri-substituted malvidin-3-glucoside and a higher percentage of cyanidin and peonidin-3-glucosides. Texture analysis showed that the viruses may increase berry-skin thickness and reduce phenol extractability. These effects carry practical implications for wine quality.